A rare case report of breast hydatid - Ali, Nawaz (Indian Journal of Case Reports, 2020)
Hydatid disease is a parasitic infection caused by the larval form of Echinococcus granulosus. Only a few reports of breast hydatid cyst are published and a majority of the reported cases have been diagnosed postoperatively as it is not possible to reach a definitive diagnosis with clinical examination and radiological investigations only. Here, we present the case report of a 35-year-old woman who presented with a painless lump in the right breast for 1-year duration. On clinical examination, a non-mobile, firm lump was detected in the right breast with no nipple retraction and axillary lymphadenopathy. This case was diagnosed as a hydatid cyst incidentally during surgery from its gross appearance which mimics that of a liver hydatid cyst, normally common in this endemic area.